Modulation of mesalamine release from enteric-coated matrix tablets using natural polysaccharides for localized colonic delivery - Sahu, Shilpa; Choudhury, Prasanta Kumar; Pasa, Gourishyam; Murthy, Padala Narasimha; Sahu, Poonam; Verma, Renuka (Creative Pharma Assent, 2024)
Background: Inflammatory bowel diseases (IBD) require effective colon-targeted drug delivery for improved therapeutic efficacy and minimized systemic side effects. Objectives: The objective of this research was to develop and evaluate novel colon-targeted matrix tablet formulations of mesalamine (5-aminosalicylic acid) for the treatment of IBD. Materials and Methods: Mesalamine matrix tablets were prepared by wet granulation technique using pH-sensitive polymers (HPMC K4M) and biodegradable natural polysaccharides (pectin, chitosan, and guar gum). Tablets were characterized for physicochemical properties, drug content, and in vitro drug release. Compatibility studies using FTIR and DSC confirmed no interaction between mesalamine and polymers. The optimized formulations were enteric-coated with Eudragit S100 and ethyl cellulose. Drug release kinetics and stability studies were conducted. Results and Discussion: The uncoated formulations (M3, M6, M7) showed adequate protection against drug release in simulated gastric (0-2 h) and intestinal (2-5 h) fluids. The enteric-coated formulations (ME3, ME6, ME7) exhibited a lag time of around 2 hours and restricted drug release (<5%) in simulated gastric and intestinal fluids up to 5 hours. However, in simulated colonic fluid (pH 6.8) containing 4% rat cecal contents, these formulations showed enhanced drug release (71-83% in 12 h) due to biodegradation of polymeric matrices by colonic enzymes. Drug release kinetics indicated anomalous transport or super case-II transport mechanisms. Stability studies at 40°C/75% RH for 3 months revealed no significant changes. Conclusion: The developed colon-targeted mesalamine matrix tablets demonstrated the potential to protect the drug from release in the upper GIT while facilitating targeted drug delivery to the colon, which could improve therapeutic efficacy and minimize systemic side effects in the treatment of IBD.